Determination of Conventional Lathe Machine Maintenance Action with the Failure and Effect Analysis Method at PT. Raja Ampat Indotim - Alif Imam Utomo; Deri Teguh Santoso; Eka Yulianty (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2022)
Over time, the condition of conventional lathes used for the production process at PT. Raja Ampat Indotim experienced a decrease in ability and function which would result in losses. However, the treatment measures carried out in PT. RAI is considered to be still ineffective, because all activities are carried out by holding treatment actions after the occurrence of damage or have no prior plans for treatment actions. So the purpose of this study is to discuss the determination of treatment actions using the Failure Mode and Effect Analysis method. 27 types of failures were obtained in conventional lathes with a maximum and minimum RPN value of 240 and 10. In order for treatment measures to be carried out effectively, treatment is focused on 8 types of failures with preventive treatment measures and also corrective treatment measures. Seiring berjalannya waktu, kondisi mesin bubut konvensional yang digunakan untuk proses produksi pada PT. Raja Ampat Indotim mengalami penurunan kemampuan dan fungsi yang akan mengakibatkan kerugian. Namun, tindakan perawatan yang dilakukan di PT. RAI dinilai masih kurang efektif, dikarenakan semua perawaatan yang dilakukan dengan mengadakan tindakan perawatan setelah terjadinya kerusakan atau tidak mempunyai rencana sebelumnya untuk tindakan perawatan. Maka tujuan penelitian ini adalah membahas tentang penentuan tindakan perawatan dengan metode Failure Mode and Effect Analysis. Didapatkan 27 jenis kegagalan yang terjadi pada mesin bubut konvensional dengan nilai RPN maksimal dan minimum sebesar 240 serta 10. Supaya tindakan perawatan dapat dilakukan secara efektif, maka penanganan difokuskan pada 8 jenis kegagalan dengan tindakan perawatan preventif dan juga tindakan perawatan korektif.